Post marketing safety assessment of the novel postpartum depression drug, Zuranolone: evidence from real-world pharmacovigilance analysis based on the FDA adverse event reporting system - Duoqin Huang; Zixin Luo; Xi Gong; Kang Zou; Yu Peng; Shaoying Zeng (Frontiers in Psychiatry)
ObjectiveZuranolone, the latest oral medication for postpartum depression, was approved in the United States in August 2023. Due to its pharmacokinetic characteristics and rapid onset of action, it is hailed as a breakthrough and enhanced version of the drug. However, there is limited information on adverse drug reactions associated with its use. The primary objective of this study is to assess the post-marketing safety of Zuranolone. This study utilizes the FAERS database to analyze the safety of Zuranolone and provide a reference for clinical safety.MethodsData on Zuranolone were collected from the FAERS database, covering the period from the third quarter of 2023 to the second quarter of 2024. Disproportionate analysis was used to quantify adverse drug reaction signals associated with Zuranolone and to detect risk signals from the data in the FAERS database. The Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Convolutional Probabilistic Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS) were used collectively to detect risk signals.ResultsThis study identified 154 reports primarily suspecting Zuranolone and 426 adverse drug events from a total of 1,626,204 adverse event (AE) reports. A total of 142 Preferred Terms (PTs) were identified across 18 System Organ Classes (SOCs). Most reports originated from the United States, with various health professionals and consumers being the main reporters. Adverse reactions following Zuranolone administration predominantly involved Nervous system disorders and Psychiatric disorders. Specific adverse reactions included Somnolence, Dizziness, Fatigue, Sedation, Suicidal ideation, Tremor, Feeling abnormal, Headache, Anxiety, and Nausea. The onset of AEs related to Zuranolone was not prolonged (average onset time of 4 days, with a median onset time of 2 days). Compared to Brexanolone, Zuranolone’s adverse reactions were more focused on nervous system diseases, while the latter was primarily associated with psychiatric disorders, General disorders and administration site conditions, and Injury, poisoning and procedural complications. Some adverse reactions related to Zuranolone were reported frequently but were not documented in the prescribing information, including Insomnia, Vertigo, Vision blurred, Migraine, and Muscle twitching.ConclusionThis study revealed potential AEs of Zuranolone, confirming known safety information about Zuranolone, providing comprehensive data for medical practice and public health decision-making, and laying the foundation for further clinical research. It also provides more comprehensive and updated evidence for the clinical safety of Zuranolone.